Trust-Based Marketing Strategy for Silver Products in Social Commerce: Integrating Customer Journey, eWOM, Live Streaming, and Price Fairness - Faisal H. Batubara (Asosiasi Dosen Muda Indonesia, 2025)
The rapid shift toward social commerce and omnichannel retailing has reshaped how consumers discover, evaluate, and purchase silver products, particularly 925 silver jewelry and gift-oriented accessories. Uncertainty related to authenticity, finishing quality, sizing, and maintenance increases perceived risk and makes trust a critical mechanism for conversion and loyalty. Objective: This study aims to formulate and empirically test an integrated marketing strategy for silver sales by (1) mapping the customer journey, (2) identifying key drivers of trust formation in social commerce, and (3) examining how trust translates into purchase and repurchase intentions under conditions of perceived price fairness. Methodology: A quantitative explanatory design was applied using an online survey of 200 valid respondents who had interacted with or purchased from a Jakarta-based silver brand (SilverLine Jewelry) through Instagram/TikTok, Shopee, and WhatsApp Business. Data were analyzed using SEM-PLS to evaluate measurement quality and test relationships among information quality, seller communication, eWOM/UGC exposure, live streaming experience, transaction security perception, trust, purchase intention, repurchase intention, and perceived price fairness. Findings: The silver customer journey is video-led at awareness (TikTok and Instagram dominate discovery), trust-led at consideration (reviews/UGC and direct chat are pivotal), and marketplace-led at conversion (marketplace checkout is most preferred), with after-sales requests forming a meaningful post-purchase touchpoint. Trust is strongly explained by controllable social commerce factors, with seller communication and information quality as the most influential drivers, followed by transaction security, while eWOM/UGC and live streaming provide significant incremental effects. Trust is the strongest predictor of purchase intention; purchase intention predicts repurchase intention; and trust also has a smaller direct effect on repurchase, indicating partial mediation. Perceived price fairness strengthens the effect of trust on purchase intention. Implications: The findings support a “trust-bundle” strategy combining transparent product specifications, responsive interaction, secure checkout options, structured social proof (UGC/reviews), live demonstrations, and standardized after-sales services (polishing/resize), reinforced by consistent fairness-oriented value communication. Originality: This research operationalizes the customer journey into a silver-specific configuration and integrates trust formation, conversion, loyalty, and price fairness within a single tested model, offering category-tailored guidance beyond generic social commerce studies.